2011
DOI: 10.2967/jnmt.110.074906
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a New 18F-FDG PET/CT Protocol in the Staging of Oral Cavity Carcinomas

Abstract: Because image fusion using 18 F-FDG PET/CT allows a better localization of the pathologic uptake, this modality has a greater sensitivity than PET alone in examining the head-neck region. However, examination of this area is particularly critical because the head and neck are close to other anatomic structures and because of the high physiologic uptake of the radiocompound. The purpose of this study was to evaluate the utility of a new imaging protocol in the staging of oral carcinoma. Methods: Thirty-four con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Cistaro et al ( 18 ) evaluated usefulness of the OM technique in patients with oral cavity carcinomas. They found that for anatomic localization and detection of tumor extent, OM images always resulted in better visualization than conventional CM images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cistaro et al ( 18 ) evaluated usefulness of the OM technique in patients with oral cavity carcinomas. They found that for anatomic localization and detection of tumor extent, OM images always resulted in better visualization than conventional CM images.…”
Section: Discussionmentioning
confidence: 99%
“…They included 34 patients with oral cavity tumors in their studies, and only one of them had lip cancer. Our study is the first and only to compare two techniques in patients with lip cancer homogeneously ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mid-morning scheduling of the examination, relaxation of muscles before the radiotracer administration, and a wait time with the patient upright may reduce the equivocal physiologic uptake generally frequent in this area. Finally, this imaging protocol seems to allow a better localization of potentially synchronous tumors [13].…”
Section: F-fdg Pet/ct (Positron Emission Tomography/computed Tomography)mentioning
confidence: 99%
“…The primary aim of the preliminary imaging of a patient with a HNSCC is to decide the clinical stage with the prominent attainable accuracy. In this concern, head-totoe 18F-FDG PET/CT (Fluorodeoxyglucose) permits the TNM stage to be discovered noninvasively in an individual process (Chang et al, 2013;Cistaro et al, 2011) Certain article have publicised excessive sensitivity and speci icity of 18F-FDG PET in association to conservative radiological standards along with the histological gold standard. (Differding et al, 2015) PET/CT PET/CT is higher to CT and MRI in inding of carcinoma of cervical lymph node metastasis, distant metastasis, remaining tumour, persevering sickness and second essential tumors causing in change in the therapy Table 2 However, the examination of FDG PET/CT investigation in the head and neck is fascinating as of the typically compound life systems, physiologic varieties, and strange design of FDG take-up following radiation treatment and medical procedure (Beltagi et al, 2019) Since FDG isn't a tumour-exact pointer, it can assemble in a range of benign progressions with benign tumours, in lammatory, post traumatic disorders.…”
Section: Positron Emission Tomography(pet)mentioning
confidence: 99%
“…On hurling the cheeks, the oral vestibule is squeezed with air, by making a negative contrast partitions of buccal and labial mucosa from the gingival mucosa, permitting both mucosal surfaces to be evaluated independently (Cistaro et al, 2011;Chang et al, 2013)…”
Section: Puffed-cheek Techniquementioning
confidence: 99%